TEOREMA PAPPUS PADA ELIPS, PARABOLA DAN HIPERBOLA - Ardiansyah Yan Hakim Nasution; Sri Gemawati; Musraini M. (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Pappus theorem is a theorem that shows collinearity of three points. The three points are the result of intersection lines that connects any six points. Any six points are divided into three points on a straight line and three points on another straight line. This paper shows that Pappus theorem is valid at a conic section (ellips, parabola and hyperbola). The properties of cross ratio are utilized to prove the validity of Pappus at the conic section.